Developing a Portable Spectrometer to Detect Chemical Contaminants in Irrigation Water - Siti Nadhirah Zainurin; Wan Zakiah Wan Ismail; Wan Aina Nadhirah Wan Azlan; Khairul Nabilah Zainul Ariffin; Wan Maryam Wan Ahmad Kamil (MDPI, 2024)
Indexed by WOS/ Scopus